(untitled) (Research, Society and Development, 2022)
The teaching of chemistry is of great importance in the formation of basic education of students, especially when the CTSA approaches are paradigmatically inserted in the school and social experience of students. In this context, the theme addressed as a general objective to carry out an analysis of journals from the google academic platform, produced in the period from 2018 to 2020, with a focus on continuing education in chemistry teaching with the Science, Technology, Society and Environment (CTSA) approach, with a view to contributing to the improvement of the teaching-learning process in the discipline of chemistry. Contextualizing the methodology specifications, 758 articles were found with the related theme. For this study, the articles were divided into three categories: instructional materials, methodological practices, continuing education. The contributions of the thematic approach can be seen in the light of the exposition of the literary base and the compatibility of scientific studies and publications, with the continuing education of chemistry teachers. The results show that the publications meet the reality of continuing education courses, since the themes highlight the main difficulties of teachers, such as the need to integrate scientific education with the citizenship education of students, releasing the teaching of chemistry through conducts traditionalist methodologies, in which they believed that the best way of teaching was defined by memorization and repetitiveness of practices.